2016
DOI: 10.1371/journal.pone.0153190
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized Controlled Trial Evaluation of a Gender Equity and Family Planning Intervention for Married Men and Couples in Rural India

Abstract: BackgroundDespite ongoing recommendations to increase male engagement and gender-equity (GE) counseling in family planning (FP) services, few such programs have been implemented and rigorously evaluated. This study evaluates the impact of CHARM, a three-session GE+FP counseling intervention delivered by male health care providers to married men, alone (sessions 1&2) and with their wives (session 3) in India.Methods and FindingsA two-armed cluster randomized controlled trial was conducted with young married cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 25 publications
7
136
0
Order By: Relevance
“…Importantly we found a striking difference between Wave 1 and Waves 2 in the IPV acceptance scores for both men and women. IPV acceptance dropped by close to 40% for both men and women between Wave 1 and Wave 2, and while this drop was greater for the intervention group, it was significant in the control group as well (see (Raj et al, 2016) for more details on intervention versus control main effect). Notably, while the acceptability of IPV decreased across all groups between Wave 1 and Waves 2, the reported IPV almost doubled for both intervention and control (though the overall rate was significantly less for the intervention group).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly we found a striking difference between Wave 1 and Waves 2 in the IPV acceptance scores for both men and women. IPV acceptance dropped by close to 40% for both men and women between Wave 1 and Wave 2, and while this drop was greater for the intervention group, it was significant in the control group as well (see (Raj et al, 2016) for more details on intervention versus control main effect). Notably, while the acceptability of IPV decreased across all groups between Wave 1 and Waves 2, the reported IPV almost doubled for both intervention and control (though the overall rate was significantly less for the intervention group).…”
Section: Resultsmentioning
confidence: 99%
“…Of those whose wives reported IPV in Wave 1 or Wave 2; however, there was little if any difference in Wave 3 reporting between treatment and control, suggesting that much of the utility of the intervention was in preventing new IPV as opposed to reducing existing IPV. This may be why the significance of the main effect in reducing physical IPV was just slightly less than statistically significant (Raj et al, 2016). In SA Table 5, we look at the trend in men’s IPV attitudes across waves, by treatment group, and IPV reporting category.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We sought to reach both female and male adolescents because previous studies have shown that family planning initiatives are more successful when both males and females are involved. 8 …”
Section: Introductionmentioning
confidence: 99%